ANALISIS SEMIOTIK KOLEKSI FOTO JURNALISTIK DALAM ARTIKEL 2014: THE YEAR IN PHOTOS - SANDAG, GIOVANNI FITZGERALD VALENSKY (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT This research which is entitled â€œAnalisis Semiotik Koleksi Foto Jurnalistik dalam Artikel 2014: The Year in Photosâ€ is focused on sign that can be found in a news photo. The aims of this research are to identify and classify kinds of sign and to analyze and describe meaning of a sign that can be found in news photo. This research uses the Peirceâ€™s theory in the process of identifying and classifying kinds of sign and the process of analyze and describe the meaning of a sign. The source of news photo was taken from aphoto essay article which is entitled 2014: The Year in Photos, published by The Atlantic on their website at www.theatlantic.com. The method of this research is descriptive method. Every sign that can be found in a news photo will be identified and classified into three kinds of sign which are index, icon, and symbol. Then, every sign meaning will be analyzed and described according to the process called semiosis. The result of this research shows that three kinds of sign which are index, icon, and symbol can be found in fifteen selected news photos, and every sign meaning from each sign found in fifteen selected news photos are different from each other. ______________________________________________________________________ Keywords: semiotic analysis, sign, kinds of sign, meaning of sign, news photo